2009
DOI: 10.1159/000262445
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Systems Approach to the Effects of Aging on Bimanual Coordination

Abstract: The present study examined the effects of aging on the execution of a bimanual coordination task in a classical phase transition paradigm in which coordination patterns (in-phase and anti-phase) and movement frequency were manipulated. Two groups of adults, the so-called young (average age 26 years) and old (average age 71 years) participants, performed both in-phase and anti-phase patterns at different frequencies. As we expected variability of relative phase was larger for older participants than for younger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 65 publications
7
33
0
Order By: Relevance
“…These findings suggest a weakening of antiphase coupling with increasing age, as observed in previous bimanual coordination studies Serrien et al, 2000;Temprado et al, 2010;Wishart et al, 2002;Wishart et al, 2000) even for bimanual force modulation. Additionally, we found that increases in hand asymmetry with age (Temprado et al, 2010) also affect bimanual force modulation. Indeed, age-related differences were higher for left hand-stimulus coupling than for the right hand-stimulus coupling and consequently the difference between hands was higher for late middle-aged participants.…”
Section: Age-related Differences In Bimanual Force Controlsupporting
confidence: 88%
See 2 more Smart Citations
“…These findings suggest a weakening of antiphase coupling with increasing age, as observed in previous bimanual coordination studies Serrien et al, 2000;Temprado et al, 2010;Wishart et al, 2002;Wishart et al, 2000) even for bimanual force modulation. Additionally, we found that increases in hand asymmetry with age (Temprado et al, 2010) also affect bimanual force modulation. Indeed, age-related differences were higher for left hand-stimulus coupling than for the right hand-stimulus coupling and consequently the difference between hands was higher for late middle-aged participants.…”
Section: Age-related Differences In Bimanual Force Controlsupporting
confidence: 88%
“…First, we expected performance would be generally lower with increasing age; we particularly assumed relative timing and relative force to be less accurate and more variable with increasing age . Second, based on previous findings (e.g., Byblow et al, 1995), we expected to observe a stronger hand-hand than hand-stimulus coupling, particularly in late middle-aged adults due to more difficulties to overcome intrinsic movement patterns and to adapt to task characteristics (Hu & Newell, 2011c); moreover, based on previous findings (Temprado et al, 2010;Wishart et al, 2000), we assumed the antiphase pattern would be less sustainable with increasing age. Third, we expected force produced at the minima would be more variable and less accurate than performance at the maxima (cf.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…All lived independently, were physically active, and did not suffer from visuomotor impairment, cognitive, or locomotor problems. They self-declared to be in good health and free of any trouble that could prevent them from doing the task and/or understanding the instructions (see Temprado et al [26] for a similar procedure). Participants of all groups had 10 years of education on average.…”
Section: Methodsmentioning
confidence: 99%
“…Greater magnitudes of noise in the system shall continuously perturb and push the movements away from in-phase and antiphase synchrony. Changes at the level of the magnitude of noise in motor systems have been often investigated as potential origins of the weaker synchronization occurring with pathologies, aging, or additional degrees of freedom for example Temprado, Vercruysse, Salesse, & Berton, 2010;Varoqui, Froger, Lagarde, Pelissier, & Bardy, 2010). Accordingly, it would be assumed that greater magnitude of noise in the movements of an actor and an environmental stimulus should be detrimental to the occurrence and stability of spontaneous visuomotor synchronization.…”
mentioning
confidence: 99%